Hubungan Asupan Nutrisi Dengan Kejadian Hipertensi Pada Ibu Hamil di Puskesmas Karangasem Kabupaten Pemalang - Habibah Khaerun Nisa; Nonik Eka Martyastuti; Dina Indrati DS (PENA NURSING, 2023)
Background: Incorrect nutritional intake is the cause of hypertension in pregnant women. Increased levels of salt and fat levels in food that trigger an increase in blood pressure. Improper nutrition can trigger the risk of rising blood pressure. Hypertension in pregnant women is divided into 2, namely mild hypertension and severe hypertension.Objective: This study aims to determine the relationship between nutritional intake and the incidence of hypertension in pregnant women.Methods: The research method uses an observational analytic method with a cross sectional approach. The sample is 30 respondents. The instrument used in this study was a 24-hour food recall questionnaire. Data analysis technique using Chi Square test.Results: The results showed that most of the nutrients were met (60.7%) with most of them having mild hypertension (53.3%). Most of the carbohydrate consumption was fulfilled (53.3%), adequate protein consumption (56.7%), and vitamin consumption was fulfilled (60.0%).